KOMPARASI KELAYAKAN FINANSIAL INDUSTRI KILANG PADI: Studi Kasus: Kecamatan Pante Ceureumen dan Kecamatan Kaway XVI Kabupaten Aceh Barat - Ikhwal Yuliandi; Yoyon, Yoyon Safrianto (Jurnal Publikasi Manajemen Informatika, 2022)
The refinery rice industry in Sub Districts Pante Ceureumen Consisting of several village were 12 units and in Sub District Kaway XVI were 18 units. The refinery refinery rice industry which is run its business players on both the area needs to be a reckoning through an analysis financial a feasibility study to see if the effort is worth or not worth, so that the purpose of this research do is to compare rates of financial worthiness refinery rice industry in Sub Districts Pante Ceureumen and Sub Districts Kaway XVI District West Aceh based on feasibility criteria Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost (Net B/C), Break Event Point (BEP) dan Payback Period (PP). The results of this study indicate that the Rizki Sejahtera Rice Refinery Industry in Pante Ceureumen District, West Aceh Regency is known discount factor level of 12 percent financially feasible to run because the IRR value is 31.08 percent, Net B/C Ratio is 1.72 and BEP and PP are smaller than the investment age of more than 20 years so that the Rizki Sejahtera Rice Refinery is able to cover the initial investment capital of the business when it is less than 20 years. While the Rimo Tani Rice Refinery Industry in Kaway XVI District, West Aceh Regency, it is known that at a discount factor rate of 12 percent, it is financially feasible to run because the IRR value is 30.20 percent, the Net B/C Ratio is 1.76 and the BEP and PP are more Smaller than the investment age of more than 20 years, so that the Rimo Tani Rice Refinery is able to cover the initial investment capital of the business when it is less than 20 years old.